DEADLINE SETTLEMENT OF PETITION FOR DECLARATION OF BANKRUPTCY BEFORE THE COMMERCIAL COURT AND THE LEGAL CONSEQUENCES ACCORDING TO LAW NUMBER 37 OF 2004 ON BANKRUPTCY AND SUSPENSION OF DEBT PAYMENT OBLIGATIONS - Tata Wijayanta (Yustisia, 2018)
This study aimed to identify and analyze (1) the regulation regarding the deadline for applications of bankruptcy, (2) the practice of the deadline regulation, and (3) the legal consequences when they do not heed the deadline. This research is a normative legal research supported by interviews with informants. The data were collected through documentation method with document study tool, while the data from the informants were collected through interviews by using interview manual tool. The secondary data were analyzed by content analysis with statute approach, while the analysis of the interview data was conducted through a qualitative analysis. The results and discussion show that the Bankruptcy and PKPU Act applies because the previous bankruptcy regulation was not effective because it did not regulate the deadline for settling bankruptcy, so that it’s  a long period of time. The regulation of deadline for bankruptcy settlement in 2015 was largely complied with the provisions of law. 87% of the verdicts (14 out of 16 verdicts) were made within less than 60 days, while 13% (2 verdicts) were made beyond the time period specified by law. The Bankruptcy and PKPU Act does not regulate any legal sanctions/effects in relation to the deadline for judges who handle bankruptcy petitions, however, the common sanctioning relates to the assessment of the judges’ performance.